2005
DOI: 10.1007/s00223-004-0231-9
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine and Dexrazoxane Enhance the Rapid Loss of Bone Mass and Further Deterioration of Vertebrae Architecture in Female Rats

Abstract: Doxorubicin (DOX) is widely used in combination cocktails for treatment of childhood hematologic cancers and solid tumors. A major factor limiting DOX usage is DOX-induced cardiotoxicity. Dexrazoxane (DXR) is an iron-binding compound and the only approved cardioprotectant for use with DOX. Amifostine (AMF) is a free radical scavenger and approved as a broad-spectrum cytoprotectant. We have shown that when female rats are treated with AMF, AMF + DOX, or AMF + DXR + DOX there is a significant decrease in the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…1B ). DOX treatment alone led to a significant 24% decrease in the BMC (p<0.01) as previously observed with female rats [ 22 ]. In order to better understand the protective effect of DXR, we decided to treat rats with DOX+DXR.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…1B ). DOX treatment alone led to a significant 24% decrease in the BMC (p<0.01) as previously observed with female rats [ 22 ]. In order to better understand the protective effect of DXR, we decided to treat rats with DOX+DXR.…”
Section: Resultssupporting
confidence: 83%
“…AMF and DXR were injected 30 min prior to the DOX injection. The choice of the DOX and AMF concentrations is based on previous work in young rats [ 24 ] and accordingly to our previous work on female rats [ 22 ]. The concentration of DXR was 20-times the concentration of DOX, a ratio previously demonstrated to reduce DOX toxicity in adult rodent [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in vitro studies and animal studies of doxorubicin have demonstrated that the agent inhibits the proliferation and differentiation of osteoblasts and selectively reduces the rate of bone formation by altering the interaction of parathyroid hormone with the osteoblast receptor [16,20,73,74]. Studies demonstrating doxorubicin's effect on bone's biomechanical properties are limited [69].…”
Section: Doxorubicinmentioning
confidence: 98%
“…In this study, specimens of rat lumbar vertebrae were analyzed with an apparent spatial resolution of 20 μm 3 using μ‐MRI combined with 3D image analysis. The choice of rat as an experimental animal model is due to the fact that it is frequently used for studies on metabolic bone diseases (23, 24) or for study of the effects of “reduced gravity,” ie, reduced weight, which induces an experimental osteoporosis when the animal is maintained tail‐suspended for long time periods (25–27).…”
mentioning
confidence: 99%